Electron transfer mediated decay in NeXe triggered by K-LL Auger decay of Ne - Stumpf, Vasili; Scheit, Simona; Gokhberg, Kirill (Chemical physics, 2017)
In this article we present the results of an ab initio study of electron transfer mediated decay (ETMD) in NeXe dimer triggered by the K-LL Auger decay of Ne. We found that the Ne2+(2p-21D)Xe and Ne2+(2p-21S)Xe states which are strongly populated in the Auger process may decay by ETMD emitting a slow electron and leading to the Coulomb explosion of the dimer which results in Ne+ and Xe2+ ions. We also computed the corresponding decay widths, the ETMD electron spectra, and the kinetic energy release of the nuclei (KER) spectra. We showed that the spectra corresponding to the decaying states which derive from the two multiplets have completely different shape which reflects differing accessibility of the ETMD final states. Thus, in the Ne2+(2p-21S)Xe state ETMD is allowed for all interatomic distances accessible in nuclear dynamics, while in the Ne2+(2p-21D)Xe state the ETMD channels become closed one by one. This in turn leads to the different behavior of the ETMD decay widths and ultimately the spectra. We show how these differences make it possible to study ETMD of the two states separately in a coincident measurement. We also discuss how the dynamics which follow ETMD in the final state manifold may lead to the appearance of the unusual products: Ne, Xe3+ and a slow electron.